Pengaruh Komitmen Organisasional terhadap Turnover Intention - Sendy Ayu Mitra Uktutias; Lilis Masyfufah; Sri Iswati (Politeknik Negeri Jember, 2021)
Human resources are valuable internal assets of the organization. Policies and efforts to maintain human resources in order to avoid turnover. The initial sign of turnoveris turnover intention. One of the predictors used to measure turnover intention is through organizational commitment. The study aims to analyze the effect of organizational commitment on employee turnover intention in the main inpatient clinic of Usada Buana Surabaya. This type of research is analytic with cross sectional design. The sample in this study was 30 employees who were taken using accidental sampling technique and analyzed using linear regression. The results showed that there was an effect of organizational commitment on employee turnover intention at the main inpatient clinic in Usada Buana Surabaya, meaning that a reduction in employee turnover intention could be done through an increase in organizational commitment. Managerial implications that can be applied are employee career development, compensation for employees who have good performance and make the work environment comfortable by scheduling family gatherings which are expected to increase organizational commitment, thereby reducing turnover intention. Keywords: Employees,Organizational, Commitment, Turnover, Intention